Concept analysis: the clarification of body adornment - Maykut, Colleen (My University, 2014)
The aim of this paper is to clarify the concept of body adornment informed by Roach’s (2002) caring theory, specifically the attribute of comportment.
Keywords: body adornment; caring; comportment; concept analysis; nurse-patient relationships